Interactive effects of defoliation and water deficit on growth, water status, and mortality of black spruce (Picea mariana (Mill.) B.S.P.) - Bouzidi, HA; Balducci, L; Mackay, J; Deslauriers, A (Springer, 2019)
Key message Defoliation followed by water deficit showed time-dependent effects on plant water status and growth in black spruce ( Picea mariana (Mill.) B.S.P.). Biotic stress negatively (during active defoliation by growing instars) and positively (after defoliation) affected plant water relations. However, water deficit, alone or combined with defoliation, prevails over defoliation-related stress for radial growth and sapling vitality.